2020
DOI: 10.1111/are.14852
|View full text |Cite
|
Sign up to set email alerts
|

Dietary guanidinoacetic acid response on digestibility, growth performance, feed utilization and carcass quality in Nile Tilapia ( Oreochromis niloticus )

Abstract: Creatine plays a vital part in the energy metabolism and physiological roles. It is exclusively found in ingredients of animal origin, so using all‐plant protein‐based diets increases the risk of creatine deficiency. The objectives of this current study were to determine the optimal level of dietary guanidinoacetic acid (GAA) with regard to the nutrient digestibility, growth performance, feed utilization and carcass quality of Nile tilapia (Oreochromis niloticus). The fish (27.33 ± 0.70 g) were fed with five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In Nile tilapia ( Oreochromis niloticus [Linnaeus]), GAA increased growth rates at 0.6–1.8 g kg −1 after 60 days of supplementation 38 . Nevertheless, in a similar study at the same concentrations, GAA did not increase growth performance or feed efficiency in this species 39 . Stites et al 33 even reported decreased weight gain, increased whole body lipid and protein as well as feed efficiency at much higher concentrations (5–20 g kg −1 ) in Red drum ( Sciaenops ocellatus [Linnaeus]).…”
Section: Application Form Of Creatinementioning
confidence: 91%
See 3 more Smart Citations
“…In Nile tilapia ( Oreochromis niloticus [Linnaeus]), GAA increased growth rates at 0.6–1.8 g kg −1 after 60 days of supplementation 38 . Nevertheless, in a similar study at the same concentrations, GAA did not increase growth performance or feed efficiency in this species 39 . Stites et al 33 even reported decreased weight gain, increased whole body lipid and protein as well as feed efficiency at much higher concentrations (5–20 g kg −1 ) in Red drum ( Sciaenops ocellatus [Linnaeus]).…”
Section: Application Form Of Creatinementioning
confidence: 91%
“…Other studies found creatine to enhance growth when used to supplement in plant‐based diets 25,26 . Still, some reports do not reflect such effects, 26,34 others are controversial 39 . In hybrid Striped bass ( Morone chrysops × Morone saxatilis ) reared in freshwater, no growth promotion or improved feed efficiency was observed, but, in fish transferred to brackish water, Burns and Gatlin reported slightly increased weight gain but no effect on feed efficiency or fillet ratio 28 .…”
Section: Effects Of Creatine and Gaa Supplementationmentioning
confidence: 99%
See 2 more Smart Citations